Development of Village Digitization through the Smart Village Concept in Permis and Rajik Villages, South Bangka Regency - Darman Saputra Darman; Julia Julia; Herdiyanti Herdiyanti (Future Science, 2022)
The rapid use of information technology in all aspects of life from the government to the community has encouraged several cities in Indonesia to implement the connectedness of the use of information technology in the form of smart cities. The development of this smart city apart from integrating all elements of the city in an information technology system that is easily accessible to the public is also for the provision of transparent, efficient and fair public services for all communities. In line with the smart city with a smaller context, namely the smart village, which is said to be smart if it innovatively uses information technology to achieve increased quality of life, efficiency and competitiveness in economic, social and environmental aspects. Permis Village, Simpang Rimba Sub-district, South Bangka Regency is a village directly adjacent to Rajik Village and Sebagin Village which is a potential village supported by a strategic location. When viewed in the context of a smart village, there is no understanding as to what ideally the concept of